Impression formation: A time-based panel study with students at a Brazilian public university - Marcos Emanoel Pereira; Elza Maria Techio (Revista de Psicología)
Published in 1946, Asch’s study was a heuristically important paradigm in the field of impression formation research, in particular for suggesting that an initial impression, even if strong enough to anchor subsequent social judgments (primacy effect), could be modified if the perceiver were offered decisive information capable of leading to a transformation of the initial impression (centrality effect). The present study reports the testing of a modified version of Asch’s paradigm, conducted over 9 years, with 667 university students from the northeast region, aiming to identify, the joint effect of a photo and the attribution of psychological traits on impression management of a fictional teacher. We can conclude that both categorization and centrality influence the formation of impressions.